Obesity and the roles of Malaysian slimming centre health technologies - Hassan, Hasliza; Sade, Abu Bakar; Rahman, Muhammad Sabbir (International Information Institute, 2016)
Malaysia is the most obese country in Asia. This can obviously be seen in urban areas where majority of people are obese. Although a lot of people are aware on this, it seems that the obesity problem is getting worse. In line with this, there are a lot of slimming centres that introducing an innovative service technology as a treatment for obesity. This research is developed through critically reviewing secondary information that was made by various research scholars and general observation in this field to propose on discovering the acceptance of people towards the service technology innovation by the slimming centre as a treatment for obesity.